An aspirin a day? Aspirin use across a spectrum of risk: cardiovascular disease, cancers and bleeds. (February 2014) - Kolber, Michael R; Korownyk, Christina
<x xml:space="preserve">Abstract</x> Aspirin or acetylsalicylic acid (ASA) is commonly used in the general population for primary prevention of cardiovascular disease (CVD). Strong evidence supports the use of ASA in secondary prevention of CVD; however, for primary prevention, potential benefits are offset by potential harms (primarily major bleeds), with no benefit in overall mortality. Anti-platelet agents, including ASA, are one of the most commonly implicated medications for hospital admissions related to adverse medication events. Studies of primary prevention in patients with risk factors for CVD also fail to show a benefit with ASA. Finally, evidence supporting ASA use for cancer prevention is limited. Health care providers should be aware of the benefits and risks associated with ASA use in primary and secondary prevention and discuss these with their patients in the context of individual patient values and preferences.